Suicidal behaviours among police officers: risk factors - Sarmento, Joana Rita Anes Tiago (2018)
Around 23% of the sampled police officers had depressive symptoms . An association was found between length of service and the level of depression because officers with a longer length of service scored higher in suicidal ideation. Overall burnout levels were high and cynicism scores were higher among officers who had no children, with statistically significant differences. Suicidal ideation scores in this sample were lower than those found in the general population